The value of somatosensory and motor evoked evoked potentials in pre-clinical spondylotic cervical cord compression - Bednarík, J; Kadanka, Z; Vohánka, S; Novotný, O; Surelová, D; Filipovicová, D; Prokes, B (European spine journal, 1998)
Previous studies have yielded conflicting data concerning the value of evoked potential parameters in the assessment of clinical relevance of cervical cord compression in clinically "silent" cases. The aim of this study was to assess the value of somatosensory (SEP) and motor evoked potentials (MEP) in the evaluation and prediction of the clinical course, by means of a 2-year follow-up prospective electrophysiological and clinical study performed in patients with clinically "silent" spondylotic cervical cord compression. Thirty patients with MR signs of spondylotic cervical cord compression but without clinical signs of myelopathy were evaluated clinically and using SEPs and MEPs during a 2-year period. The results of the study showed that SEPs and MEPs documented subclinical involvement of cervical cord in 50% of patients with clinically "silent" spondylotic cervical cord compression. During the 2-year period clinical signs of cervical myelopathy were observed in one-third of patients with entry EP abnormality in comparison with no patients with normal EP tests. Combined SEPs and MEPs proved to be a valuable tool in the assessment of the functional relevance of subclinical spondylotic cervical cord compression. Normal EP findings predict a favourable 2-year clinical outcome.
Keywords: komprese míchy; Evoked Potentials, Somatosensory; osteofytóza páteře; motorické evokované potenciály; Male; Time Factors; Evoked Potentials, Motor; Sensitivity and Specificity; mužské pohlaví; studie případů a kontrol; Spinal Osteophytosis; Prospective Studies; Spinal Cord Compression; Follow-Up Studies; somatosenzorické evokované potenciály; následné studie; ženské pohlaví; Humans; prospektivní studie; elektromyografie; Electromyography; časové faktory; senzitivita a specificita; krční obratle; Female; Cervical Vertebrae; lidé; Case-Control Studies